2017
DOI: 10.1098/rsos.170517
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor performance of cane toads differs between native-range and invasive populations

Abstract: Invasive species provide a robust opportunity to evaluate how animals deal with novel environmental challenges. Shifts in locomotor performance—and thus the ability to disperse—(and especially, the degree to which it is constrained by thermal and hydric extremes) are of special importance, because they might affect the rate that an invader can spread. We studied cane toads (Rhinella marina) across a broad geographical range: two populations within the species' native range in Brazil, two invasive populations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 56 publications
3
46
0
2
Order By: Relevance
“…In a previous study, we showed that locomotor performance of wild‐caught cane toads differed among populations from Brazil, Hawai'i, and four locations within Australia (Kosmala et al., ). However, we were unable to identify the proximate basis for that divergence; it might have been entirely due to toads acclimating to the conditions they experience during ontogeny.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In a previous study, we showed that locomotor performance of wild‐caught cane toads differed among populations from Brazil, Hawai'i, and four locations within Australia (Kosmala et al., ). However, we were unable to identify the proximate basis for that divergence; it might have been entirely due to toads acclimating to the conditions they experience during ontogeny.…”
Section: Discussionmentioning
confidence: 89%
“…This protocol is described in more detail by Kosmala et al. (). All procedures were approved by the University of Sydney Animal Care and Ethics Committee (Protocol # 703) and by Charles Darwin University Animal Ethics and Welfare Committee (AEWC) (Protocol # A13016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Any population that expands rapidly into hitherto uncolonised territory is likely to experience powerful new evolutionary pressures. Some of those novel challenges result from encounters with new types of predators, pathogens, prey and competitors (Brown, Kelehear, & Shine, ; Lee & Klasing, ; Sakai et al., ; Strauss, Lau, & Carroll, ), whereas others are driven by novel abiotic conditions (Kosmala, Christian, Brown, & Shine, ) or by the process of range expansion itself (Shine, Brown, & Phillips, ). In response to such demands, many invasive species demonstrate rapid phenotypic changes, via either developmental plasticity or adaptation, that enhance the ability of invasion‐front individuals to deal with those novel challenges (e.g.…”
Section: Introductionmentioning
confidence: 99%